LANGUAGE POLITENESS STRATEGIES IN TEACHER-STUDENT CLASSROOM COMMUNICATION: A PRAGMATIC DISCOURSE ANALYSIS OF INTERACTIONAL FUNCTIONS - Nurmairina Nurmairina; Dinda Yarshal (SENSEI RESEARCH CENTER, 2024)
Language politeness is an essential component of classroom communication because it shapes teacher-student relationships, learning participation, emotional safety, and instructional effectiveness. In classroom interaction, teachers need to manage instruction, discipline, feedback, and questioning without damaging students' face or reducing their willingness to participate. However, classroom communication often contains directives, corrections, reprimands, and evaluations that may become face-threatening if they are not expressed through appropriate politeness strategies. This study aims to analyze language politeness strategies in teacher-student classroom communication and examine their pedagogical and relational functions. The study employed a qualitative pragmatic discourse analysis involving classroom observations, audio-video recordings, teacher interviews, student focus group discussions, and field notes. The participants consisted of three English teachers and 96 secondary school students. The data were analyzed using Brown and Levinson's politeness framework supported by relational work theory. The findings revealed that teachers and students used four major politeness strategies: positive politeness, negative politeness, bald-on-record strategy, and off-record strategy. Positive politeness was the most dominant strategy because it helped build solidarity, encourage participation, and create supportive classroom rapport. Negative politeness appeared in requests, corrections, and feedback to reduce imposition. The study concludes that politeness strategies are pedagogical resources for managing face, authority, participation, and classroom harmony.